Influence of six rootstocks on growth of six scion clones of rubber tree a preliminary report - Gonçalves, Paulo de Souza; Martins, Antonio Lucio Mello; Gorgulho, Eliana P; Bortoletto, Nelson; Bermond, Guilherme (Pesquisa Agropecuaria Brasileira, 1994)
This paper is a preliminary evaluation on growth of a rootstock vs. scion interaction study of rubber tree [Hevea brasiliensis (Willd. ex Adr. de Juss.) Müell. Arg.] trial of six scions: IAN 873, GT 1, RRIM 701, PB 235, RRIM 600 and PR 107 grafted on to six rootstocks IAN 873, GT 1, RRIM 600, RRIM 701, PB 235 and unselected seedling in all combinations. The trial was established in the experimental fields at the Pindorama Experimental Station, SP, Brazil, under randomized complete blocks in split-plot design, where the main plot was the rootstocks and the sub-plots the scions. The results showed in the first year of evaluation that IAN 873 rootstock showed the best performance at the different scions. Compared with the RRIM 600 rootstocks, IAN 873 was 10% and 12% superior in girth and height, respectively. The poorest performing rootstocks PB 235 measured 11% lower than IAN 873 in girth. Rootstocks from RRIM 600 and RRIM 701 showed scions with less vigour.